Establishment of goat infection model of the peste des petits ruminants virus isolated in China for vaccine efficacy evaluation - Xue Wang; Hefeng Chen; Xianfeng Zhang; Zhengshuang Wu; Shuai Zhang; Lei Shuai; Lulu Wang; Weijie Li; Jinliang Wang; Wenxing Liu; Xijun Wang; Zhiyuan Wen; et al. (Journal of Integrative Agriculture)
In 2013, peste des petits ruminants (PPR) re-emerged in China and spread to the majority of provinces across the country. The disease was effectively controlled through a vaccination campaign employing live attenuated vaccines, although sporadic cases still occurred. However, limited information is currently available regarding the peste des petits ruminants virus (PPRV) endemic in China. Here, a PPRV strain (HLJ/13) was isolated from a field sample in China using Vero cells expressing goat signalling lymphocyte activation molecule. Phylogenetic analysis indicated that HLJ/13 belonged to lineage IV. Subsequent intranasal and subcutaneous inoculation of goats with a dose of 2×106 TCID50 of HLJ/13 resulted in the development of typical clinical symptoms of PPR, including pyrexia, ocular and nasal discharges, stomatitis, and diarrhea. All infected goats succumbed to the disease by day 8. To gain further insight, viral loading, pathological examination and immunohistochemical analyses were conducted, elucidating the main targets of HLJ/13 as the respiratory system, digestive tract and lymphoid organs. Employing the goat infection model established above, the goat poxvirus-vectored PPR vaccine, which was previously developed and could be used as DIVA (differentiating infected from vaccinated animals) vaccine, provided complete protection against the challenge of HLJ/13. It is important to note that this study represents the first comprehensive report delineating the biology and pathogenicity characterization, and infection model of PPRV isolated in China.